Pediatric Primary Care Mental Health Specialist Examination: Job Task Analysis. - Hallas, Donna; Heuer, Beth; Sesay-Tuffour, Sheri A.; Foerster, Lillian Adele (Journal for Nurse Practitioners, 2023)
Developmental, behavioral, and mental health (DBMH) conditions among pediatric populations have increased in prevalence in primary care. Approximately 1 in 5 children have mental health conditions, but only 20% receive care. In October 2021, a national emergency in children's mental health was declared. The Pediatric Nursing Certification Board offers a pediatric primary care mental health specialist (PMHS) examination that validates the knowledge, skills, and abilities of certified nurse practitioners caring for children, adolescents, and young adults with DBMH conditions. This review describes the methodology, data analysis, and results of the job task analysis that ensures examination quality measuring preparedness to practice as a certified PMHS. • Behavioral and mental health conditions have increased in the pediatric populations. • Job task analysis verifies content for the pediatric PMHS certification examination. • Details for the PMHS exam content, (eg, Screenings, Dx, RX, etc.) are identified. • Knowledge, skills, and abilities to provide safe effective care are tested.